Physiological response of one of South Africa's premier freshwater sport angling species, the Orange-Vaal smallmouth yellowfish Labeobarbus aeneus, to catch-and-release angling. Issue 1 (2nd January 2016) - Smit, Nico J; Gerber, Ruan; Greenfield, Richard; Howatson, Glyn
Abstract : The practice of catch-and-release fishing has been widely promoted by angling fraternities as a fisheries manage- ment tool. The aim of this investigation was to determine the physiological response of Orange-Vaal smallmouth yellowfish, Labeobarbus aeneus, to catch-and-release angling in the Vaal River, South Africa. Fish were collected using standard fly-fishing techniques, anaesthetised in clove oil and blood was drawn from the caudal vein; thereafter the fish were weighed, measured, revived and released. Blood plasma was analysed for concentra- tions of glucose, cortisol and lactate to determine the effects of angling duration, fish size and water tempera- ture. Larger fish were angled for a longer duration compared with smaller fish. Levels of glucose were affected by water temperature (influenced by time of year). Plasma glucose concentrations decreased with greater angling duration. Few individuals ( n = 12) showed increased plasma cortisol concentrations. In extended-capture fish (angled for >1 min), lactate concentrations increased significantly above values for rapid-capture fish (angled for >30 s). These data suggest that catch-and-release causes physiological stress to fish, but nonetheless this practice can be a valuable fisheries management tool to ensure the sustainability of fish populations. Other factors beyond the 'angling' time are likely to contribute to physiological disruptions in homeostasis and therefore handling and air exposure of angled fish should be included in future catch-and–release angling studies. In addition, the longer-term impact of angling on fish health should also be determined.